Sex-related differences in cardiac and myofilament function in rats with pressure-overload induced left ventricular hypertrophy. (25th November 2020) - Radovits, T; Ruppert, M; Olah, A; Sayour, A.A; Barta, B.A; Szabo, G; Bodi, B; Papp, Z; Merkely, B
Abstract: Introduction: Recent findings indicate that sex is a major determinant of left ventricular (LV) structure in pressure overload (PO)-induced LV myocardial hypertrophy (LVH). However, data are scare regarding sex-related differences in LV function in case of PO-evoked LVH. Aim: Hence, in the present study we aimed at comprehensively investigating sex-related functional differences on the global cardiac level and also on the myofilament level in PO-induced LVH. Method: Abdominal aortic banding (AB) was carried out to induce chronic PO for 6 or 12 weeks in male and female rats. Age- and sex-matched sham-operated animals served as controls. The development of LVH was followed by serial echocardiography. The extent of cardiomyocyte hypertrophy and myocardial fibrosis were evaluated by histology. Cardiac function was assessed by pressure-volume analysis. Force measurement was carried out in permeabilized cardiomyocytes to compute myofilament function. Results: At week 6, robust myocardial hypertrophy, concentric LV geometry and moderate interstitial fibrosis were detected in both male and female AB rats. This early stage of PO-induced LVH was associated with increased LV contractility (slope of end-systolic pressure-volume relationship [ESPVR, mmHg/μl]: 3.09±0.18 Male-AB-wk6 vs. 1.79±0.22 Male-Sham-wk6 P<0.05; 3.68±0.77 Female-AB-wk6 vs. 1.87±0.21 Female-Sham-wk6 P<0.05) and enhanced myofilament Ca2+ sensitivity in both sexes (pCa50: 5.86±0.01 Male-AB-wk6 vs. 5.73±0.02 Male-Sham-wk6 P<0.05; 5.94±0.03 Female-AB-wk6 vs. 5.73±0.01 Female-Sham-wk6 P<0.05). At week 6, the augmented LV contractility effectively counterbalanced the increased afterload in both male and female AB groups. Hence, ventricular-arterial coupling (VAC) was maintained and LV systolic function was preserved in the AB groups in both sexes. In contrast, at week 12, marked sex differences could be observed. At this later stage, LVH was characterized by eccentric remodeling and intensified collagen accumulation in male AB rats. The initial LV contractility augmentation (slope of ESPVR, mmHg/μl: 1.74±0.13 Male-AB-wk12 vs. 1.31±0.17 Male-Sham-wk12 n.s.) as well as the enhanced myofilament Ca2+ sensitivity (pCa50: 5.78±0.02 Male-AB-wk12 vs. 5.75±0.01 Male-Sham-wk12 n.s.) diminished, leading to impaired VAC and reduced LV systolic function. On the contrary, in female AB rats, cardiac contractility (ESPVR, mmHg/ μl: 3.97±0.50 Female-AB-wk12 vs. 2.08±0.17 Female-Sham-wk12 P<0.05) and myofilament Ca2+ sensitivity (pCa50:5.85±0.02 Female-AB-wk12 vs. 5.78±0.01 Female-Sham-wk12 P<0.05) remained increased, resulting in adequate VAC and preserved LV systolic function at late-stage of PO-induced LVH as well. Conclusion: The initially augmented LV contractility and enhanced myofilament Ca2+ sensitivity declines in male but not in female AB rats at later time points. Hence, characteristically different alterations occur in LV systolic function between the two sexes in late-stage of PO-evoked LVH. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): NVKP_16-1-2016-0017.